Experimental and numerical studies of thermal performance enhancement in the receiver part of solar parabolic trough collectors. (September 2017) - Kumaresan, G.; Sudhakar, P.; Santosh, R.; Velraj, R.
Abstract: A solar collector is a device which helps to harnesses solar radiation into useful form of energy. Among various solar collectors, the parabolic trough collector (PTC) is considered to be the best option for medium temperature (150–400 °C) heat requirements. The popularity of solar parabolic trough technology has generated interest in higher efficiency energy recovery potential. The absorber tube, also called the receiver tube or heat collection element, is one of the main functional units of a solar PTC in addition to other elements like parabolic mirrors, metal support structure and tracking unit assembly. Parabolic mirrors reflect to a focal point and concentrate falling sun rays onto an absorber tube, which is made up of a long metallic structure covered by an evacuated glass envelope to reduce convective heat transfer losses. Many techniques were attempted to enhance the heat transfer potential in the receiver tube portion of a solar PTC which includes techniques such as half insulation receiver, cavity receivers, vacuum outer shell, inclusion of inserts, baffles, artificially roughened sinks, selective coatings etc. In some of the research works, nanoparticles were also used to enhance heat transfer properties of the heat transfer fluid. In this paper, detailed review of the experimental and numerical works carried out on heat transfer enhancement techniques which focus on minimization of heat loss, use of turbulators, addition of nanofluid and selective coatings in the receiver tube of a solar PTC are presented. Further the major reasons for heat loss in the receiver tube and comparative study of various heat transfer enhancement techniques are summarised.